Genetic divergences among buffalo sires for beef production considering their offspring growth traits in Brazil - Ferraz Filho, Paulo Bahiense; Ramos, Alcides de Amorim [UNESP]; Souza, Júlio César de; Malhado, Carlos Henrique Mendes; Freitas, José Antonio de (My University, 2010)
The genetic divergence of 30 buffalo sires were evaluated based on their expected offspring differences regarding the development characteristics using the multivaried analysis. Six similar genetic groups were obtained. It was also identified the genotype that presented dissimilarity for matings that aimed at either the hybrid vigor or the heterosis.
Keywords: Sires’ choice; Main components; Cluster analyses